Influences of Macroeconomic and Local Factors on House Price Growth Rate Volatility - Ghatak, Sananda. (2017)
Abstract: The paper aims to identify the factors influencing variation in house price growth rate in Metropolitan and Micropolitan Statistical Areas in the United States. It helps to identify how town characteristics interact with macroeconomic conditions to influence volatility. Towns are defined as college, retirement and industrial towns based on demographic data and low elasticity based on housing supply elasticity. Macroeconomic factors studied are both at a local and national level. I have built a GARCH model to estimate volatility for each year of each CBSA. Using the predicted volatility a panel data regression model is used to study the impact of these macroeconomic variables across these towns. The results show that that national macroeconomic variables affect volatility whereas local variables are not statistically significant for all towns. Also the business cycles and housing cycles impact volatility in these towns differently.; Thesis (M.S.)--Tufts University, 2017.; Submitted to the Dept. of Economics.; Advisor: Jeffrey Zabel.; Committee: Marcelo Bianconi.; Keyword: Economics.